It's Holman vs Sharpe - Unknown (Sunday Express)
The Pan Jumbie talks about his Panorama 1988 experience. The article recounts how in 1972 Ray Holman, was the first man to arrange his own composition in a Panorama contest and how Boogsie Sharpe, who more or less grew up in Starlift, had moved on, to form Phase II, with the younger generation in 1973.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Arrangers (Musicians) -- Trinidad and Tobago